2021
DOI: 10.13189/cea.2021.090205
|View full text |Cite
|
Sign up to set email alerts
|

An Optimum Thermal Insulation Type and Thickness for Residential Buildings in Three Different Climatic Regions of Saudi Arabia

Abstract: Efficient thermal insulation in the harsh desert climate of Saudi Arabia, where the cooling requirement of buildings is dominant, is very important from the aspect of energy efficiency. Through its eco-friendly properties, thermal insulation is one of the most efficient strategies for reducing energy use while providing the desired thermal comfort. In this study, the impact of thermal insulation type and thickness on reducing the annual energy consumption was evaluated for a sample prototype building located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…29 Due to the inadequate thermal envelope of buildings in Saudi Arabia, air conditioning systems consume a significant amount of energy. 27,30,31 As a result, there is significant potential for optimizing energy usage and ensuring thermal comfort in school buildings, which will depend on factors such as their typology and occupancy patterns. 32 Saudi Arabia ranks within the top 20 globally in terms of both electricity production and consumption.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Due to the inadequate thermal envelope of buildings in Saudi Arabia, air conditioning systems consume a significant amount of energy. 27,30,31 As a result, there is significant potential for optimizing energy usage and ensuring thermal comfort in school buildings, which will depend on factors such as their typology and occupancy patterns. 32 Saudi Arabia ranks within the top 20 globally in terms of both electricity production and consumption.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…According to the study conducted by Al-Tamimi, 31 XPS finds widespread utilization within the KSA construction sector, notably in roofing systems. This prevalence is attributed to its cost-effectiveness, straightforward manufacturing process and ease of installation.…”
Section: Energy Efficiency Measures Of the External Wall’s Insulationmentioning
confidence: 99%
“…Additionally, it focused on floors, walls, and roofs, and only 1-2 rooms in the building were examined. Al-Tamimi [22] determined the most effective way of using thermal insulation in building envelopes for residential buildings under different climate conditions. Additionally, four different insulation materials were used to perform economic modelling and lifecycle cost analysis.…”
Section: Energy Efficiency Measures In Saudi Arabiamentioning
confidence: 99%
“…The results showed that the best insulation material is Rockwool, which has the highest percentage of reducing the internal room temperature by 3.85%. A study achieved by Al-Tamimi [12] in the Kingdom of Saudi Arabia of a building using a simulation method to study the effect of the thickness of a type of thermal insulation XPS Extruded Polystyrene on energy saving and the cost. The study was in three different climates in the Kingdom: hot and dry, hot and humid, and temperate.…”
Section: Introductionmentioning
confidence: 99%